Computer Aided Simulation Analysis For Computation Of Modal Analysis Of The Freight Wagon - Stastniak, Pavol; Harusinec, Jozef (Communications - Scientific letters of the University of Zilina, 2013)
This paper deals with theoretical and practical aspects of modal analysis, which belongs to the tests for design of new rail wagons. The paper describes the process for calculating the eigenfrequencies of the wagon with non-standard design and dimensions and strength analysis of the modified construction of bogie type Y25. This computer aided simulation analysis significantly reduces the time to verify the static and dynamic evaluation of rail vehicles.